Phenethyl Isothiocyanate and Cisplatin Co-Encapsulated in a Liposomal Nanoparticle for Treatment of Non-Small Cell Lung Cancer - Sun, Mengwei (Molecules, 2019)
Lung cancer is the leading cause of cancer-related death in the Unites States, and approximately 85% of all lung cancers are classified as non-small cell lung cancer (NSCLC), which is extremely difficult to treat and its survival rate is low. After decades of clinical trials, the most effective treatments are still those that implement the first-generation platinum anticancer agent cisplatin (CDDP) in combination with other drugs. We previously demonstrated that the naturally-occurring compound phenethyl isothiocyanate (PEITC) can be used to sensitize NSCLC cells to CDDP. Furthermore, co-encapsulation of PEITC and CDDP in liposomes enhances their toxicity toward NSCLC cells. We here optimize liposomal-PEITC-CDDP, demonstrate the release of PEITC and CDDP from the nanoparticle, and show that liposomal-PEITC-CDDP is much more toxic toward both A549 and H596 human NSCLC cell lines than toward WI-38 and BEAS-2B human normal lung cell lines. Thus, we have prepared an efficacious therapy that has significantly higher toxicity toward cancer cell lines than normal cell lines.